Baseline MNREAD Measures for Normally Sighted Subjects From Childhood to Old Age - Calabrèse, Aurélie; Cheong, Allen M Y; Cheung, Sing-Hang; He, Yingchen; Kwon, MiYoung; Mansfield, J Stephen; Subramanian, Ahalya; Yu, Deyue; Legge, Gordon E (Investigative ophthalmology & visual science, 2016)
The continuous-text reading-acuity test MNREAD is designed to measure the reading performance of people with normal and low vision. This test is used to estimate maximum reading speed (MRS), critical print size (CPS), reading acuity (RA), and the reading accessibility index (ACC). Here we report the age dependence of these measures for normally sighted individuals, providing baseline data for MNREAD testing. We analyzed MNREAD data from 645 normally sighted participants ranging in age from 8 to 81 years. The data were collected in several studies conducted by different testers and at different sites in our research program, enabling evaluation of robustness of the test. Maximum reading speed and reading accessibility index showed a trilinear dependence on age: first increasing from 8 to 16 years (MRS: 140-200 words per minute [wpm]; ACC: 0.7-1.0); then stabilizing in the range of 16 to 40 years (MRS: 200 ± 25 wpm; ACC: 1.0 ± 0.14); and decreasing to 175 wpm and 0.88 by 81 years. Critical print size was constant from 8 to 23 years (0.08 logMAR), increased slowly until 68 years (0.21 logMAR), and then more rapidly until 81 years (0.34 logMAR). logMAR reading acuity improved from -0.1 at 8 years to -0.18 at 16 years, then gradually worsened to -0.05 at 81 years. We found a weak dependence of the MNREAD parameters on age in normal vision. In broad terms, MNREAD performance exhibits differences between three age groups: children 8 to 16 years, young adults 16 to 40 years, and middle-aged to older adults >40 years.